A Cost-Effectiveness Analysis of Screening Strategies Involving Non-Invasive Prenatal Testing for Trisomy 21 - Wang, Shuxian; Liu, Kejun; Yang, Huixia; Ma, Jingmei (Frontiers in Public Health, 2022)
Introduction: In accordance with social development, the proportion of advanced maternal age (AMA) increased and the cost of Noninvasive Prenatal Testing (NIPT), decreased. Objective: we aimed to investigate the benefits and cost effectiveness of NIPT as primary or contingent strategies limited to high risk population of trisomy 21 (T21). Methods: Referring to parameters from publications or on-site verification, a theoretical model involving 1,000,000 single pregnancies was established. We presented five screening scenarios, primary NIPT (Strategy 1), contingent NIPT after traditional triple serum screening higher than 1/300 or 1/1000 (Strategy 2-1 or 2-2) and age-based Strategy 3. Strategy 3 was stratified, in which 1) for advanced maternal age (AMA) of 40 and more, diagnostic testing was offered, 2) for AMA of 35 to 39, NIPT was introduced, 3) if younger than 35, contingent NIPT with risk higher than 1:300 (Strategy 3-1) or 1:1000 (Strategy 3-2) will be offered. The primary outcome was incremental cost analysis on baseline and alternative assumptions, taking aging society, NIPT price and compliance into consideration. The strategy was “appropriate” when the incremental cost was less than costs for raising one T21 child (0.215 million US). The second outcomes included total cost, cost-effect, cost-benefit analysis and screening efficiency. Results: Strategy1 was costly, while detected most T21. Strategy2-1 reduced unnecessary PD and was optimal in total cost, cost-effect and cost-benefit analysis, nevertheless T21 detection was the least. Strategy3 induced most PD procedures. Then setting Strategy2-1 as baseline for incremental cost analysis, Strategy3-1 was appropriate. In sensitivity analysis, when NIPT price was lower than 47 US, Strategy1 was the most appropriate. In society with more than 20% proportion of older than 35, the incremental cost of Strategy3-2 was proper. Conclusion: Combined strategies involving NIPT reduced unnecessary diagnostic tests. AMA proportion and NIPT price were the key roles in strategy decision. Age-based strategy was optimal in incremental cost analysis and presented to be prominent as AMA proportion and NIPT acceptance increased. The primary NIPT was most effective, while only with certain price, it became the most cost-effective strategy.